Classroom discourse analysis as a tool for exploring ethical tensions in a critical teaching. Issue 2 (2nd April 2020) - Soto, Carlos
ABSTRACT: This article presents classroom discourse analysis as a tool for critical teacher education. It argues that such analysis can raise awareness of how teachers live out their ethical commitments in classroom–level interactions, but needs to be carefully situated. Drawing on the author's research conducted while teaching junior secondary students in Hong Kong, the article weaves classroom discourse analysis into a critical incident reflection focusing on ethical tensions that emerge from a class activity exploring dehumanisation. The activity used a pedagogy of discomfort in order to unsettle students' beliefs and practices, but in facilitating the activity, the teacher's ethic of care was also challenged.